The Effectiveness of Proprioceptive Training for Improving Motor Performance and Motor Dysfunction: A Systematic Review - Winter, Leoni; Huang, Qiyin; Sertic, Jacquelyn V. L.; Konczak, Jürgen (Frontiers in Rehabilitation Sciences, 2022)
Objective Proprioceptive training is any intervention aiming to improve proprioceptive function with the ultimate goal to enhance motor function and performance. It has been promoted as an approach to enhance athletic performance and as a tool for sensorimotor rehabilitation. Numerous studies sought to provide evidence on the effectiveness of the approach. However, many different training regimes claiming to train proprioception report a variety of sensorimotor measures that are not directly comparable. This, in turn, makes it difficult to assess effectiveness across approaches. It is the objective of this study to systematically review recent empirical evidence to gain an understanding of which outcome measures are most sensitive, which populations may benefit most from proprioceptive training, and what are the effects on proprioceptive and motor systems. Methods Four major databases were searched. The following inclusion criteria were applied: (1) A quantified pre- and post-treatment measure of proprioceptive function. (2) An intervention or training program believed to influence or enhance proprioceptive function. (3) Contained at least one form of treatment or outcome measure that is indicative of somatosensory function and not confounded by information from other sensory modalities. 4) The study reported of at least one quantified measure of motor performance. Results Of the 3,297 articles identified by the database search, 70 studies met the inclusion criteria and were included for further review. Across studies, proprioceptive training led to comparable gains in both proprioceptive (+46%) and motor performance (+45%). The majority of studies (50/70) applied active movement interventions. Interventions applying somatosensory stimulation were most successful in clinical populations. Joint position sense error (JPSE) was the most commonly used proprioceptive measure and presents a reliable and feasible measure for clinical use. Conclusion Proprioceptive training can lead to significant improvements in proprioceptive and motor function across a range healthy and clinical populations. Regimens requiring active movement of the trainee tended to be most successful in improving sensorimotor performance. Conclusive evidence on how long training gains are retained is still lacking. There is no solid evidence about the underlying long-term neuroplastic changes associated proprioceptive training.